Experimental Study of Radiation From Coated Turbine blades - Husain Al-taie, Arkan Khilkhal (Cranfield University, 1990)
The specific power (or specific thrust) of modern gas turbines is much influenced by the gas temperature at turbine inlet. Even with the use of the best superalloy available and the most advanced cooling configurations, there are competitive pressures to operate engines at even higher gas temperatures. Ceramic coatings operate as thermal barriers and can allow the gas temperature to be increased by 50 to 220 K over the operating gas temperature for an uncoated turbine . It is important that the surface temperature of the blade be determined as accurately as possible. Large uncertainties as to the surface temperature require significant margins for safe operation . Blade surface temperatures can be determined with an accuracy of 10 K using radiation pyrometry and about"30 to 40 K by calculating the blade temperature based on---gas temperature measurement of the exhaust gas plane. This'- makes pyrometry an attractive option for advanced high temperature gas turbines . However, there is little experience in measuring surface temperatures of blades coated with ceramic coatings. There is evidence that the. radiation signal picked up by the pyrometer will not only depend on the surface temperature but also on a number of optical properties of the coating. Important among these are the emissivity of the coating and whether the coating is translucent. Parameters affecting this are the coating material, coating surface finish, coating thickness and whether or not a bond coat is used . This work explores these variables in a rig that simulates the conditions within a turbine stage of a gas turbine engine. In which six thermal barrier coating systems were tested. These systems are of current interest to gas turbine manufacturers and users. They include the latest advances in coating technology. Four stabilized zirconia systems and two alumina based systems were tested. It was found experimentally that the surface emissivity of these coating systems was invariant over the range 873 to 1023 K surface temperature. It was found that the use of different stabilizers did not affect the surface spectral emissivity. In further experiments six turbine wheels were coated with these systems and tested at turbine entry temperatures of 973, 1073, and 1173 K. It was found that the blade surface temperature was function of the coating material, coating thickness and turbine entry temperature. The blade surface temperature was also function of the blade height being maximum at the blade tip and minimum at the blade root . It was found that the C-YPSZ was better insulator than the rest of the systems. Whilst the blades coated with zirconia based systems suffered minor loss near the edges, the two alumina based systems were lost from more than a blade during the test. This coating loss was picked up by. the pyrometer . Analysis shows that the measured blade surface temperature was within 10 K of that calculated. The use of 0.3 mm of C-YPSZ on air cooled turbine blades caused 250 K surface temperature increase and 270 K metal temperature decrease for turbine entry temperature of 1673 K. The metal temperature reduction was as high as 310 K for coating thickness of 0.5 mm.